The vulnerability of water resources management as a result of climate change in Chiang Rai province - Mongkonkorn Srivichai (Journal of Current Science and Technology, 2016)
This article provides an overview of a study undertaken in Bandu, Chiang Rai into potential climate change effects and the involvement of the community in water resource management to demonstrate the vulnerability of the area to cope with climate change related events such as flooding, etc. The Providing Regional Climates for Impacts Studies (PRECIS) model based on Scenario B2 was used to predict likely weather patterns and events. This modeling showed that for the period 2014 to 2023, there will be a tendency for average annual rainfall to increase by up to 86% over that shown in the historical records for the previous thirty years. Coupled with the increase in rainfall will be a rise in average maximum and minimum temperatures of 1 to 4 degrees centigrade. These increases in temperature and rainfall will impact on the water infrastructure’s ability to cope with the demands. In this study, the researchers administered a survey questionnaire to the local villagers in the Bandu Municipal District, Chiang Rai. Analysis of the survey data reveals that the local people feel aware of the changes that are occurring in their communities but feel that they have no opportunity to participate in the planning and development of the water infrastructure. Consequently, this is likely to result in an increase into the severity of future disasters such as flooding. In response to this increase in severity, the communities will need to make preparations to respond to such events. This includes adapting their lifestyles to enable them to live with future changes.